2011
DOI: 10.1039/c1nr10930h
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic synthesis of chiral erbium-doped silver/peptide/silica core-shell nanoparticles (ESPN)

Abstract: Peptide-modified silver nanoparticles have been coated with an erbium-doped silica layer using a method inspired by silica biomineralization. Electron microscopy and small-angle X-ray scattering confirm the presence of an Ag/peptide core and silica shell. The erbium is present as small Er(2)O(3) particles in and on the silica shell. Raman, IR, UV-Vis, and circular dichroism spectroscopies show that the peptide is still present after shell formation and the nanoparticles conserve a chiral plasmon resonance. Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…The main challenge is to help to the design by chemical pathways of new multifunctional nanomaterials providing opportunities, for example, in the field of sensors or imaging. [46,[150][151][152][153][154][155] Thus, inorganic, supramolecular or biomimetic systems were inserted within lamellar hybrid based hydroxides. [46,153,[156][157][158][159] Here it is important to evaluate the effect of confinement on the structure or properties of the inserted compounds, and their sensitivity to external stimuli.…”
Section: Structuring and Functionalization Of Solidmentioning
confidence: 99%
“…The main challenge is to help to the design by chemical pathways of new multifunctional nanomaterials providing opportunities, for example, in the field of sensors or imaging. [46,[150][151][152][153][154][155] Thus, inorganic, supramolecular or biomimetic systems were inserted within lamellar hybrid based hydroxides. [46,153,[156][157][158][159] Here it is important to evaluate the effect of confinement on the structure or properties of the inserted compounds, and their sensitivity to external stimuli.…”
Section: Structuring and Functionalization Of Solidmentioning
confidence: 99%
“…These particles offer several advantages in terms of narrow size distribution and defined shape. In addition, further modifications of these SNP are possible to obtain more complex coreshell type nanoparticles Mantion et al 2011). The particles can be easily obtained in a reproducible way and also in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…They could further show that the obtained peptide-coated AgNPs can be coated with a silica shell retaining the chiral information carried by the coated AgNPs 149 and that the incorporation of erbium into this shell leads to the formation of paramagnetic and chiral AgNPs. 150 Recently, Upert et al 151 reported the use of oligoprolines as scaffolds for the size-controlled formation of AgNPs with the diameter of the AgNPs correlating with the length of the aldehyde-functionalized helical peptides. The aldehyde functions are used in a Tollens reaction to reduce the silver ions to AgNPs that are stabilized by the resulting carboxylic acids.…”
Section: 137mentioning
confidence: 99%